MIXED METHODS RESEARCH ON EXPERIENCES OF FOREIGN-EDUCATED KAZAKHSTANI GRADUATES IN THE LOCAL LABOUR MARKET - Tolesh, Fariza (Graduate School of Education, 2018)
Study abroad is a well-researched phenomenon however the existing literature does not specifically illustrate the extent of an impact of foreign education on employment experiences of full degree graduates from developing countries such as Kazakhstan when they return to their home labour markets. The current educational policy of Kazakhstan is oriented toward internationalisation of higher education, thus, the government is actively encouraging young people to study abroad. Consequently, the number of people with international education is growing within the country’s labour force. Generally, study abroad is viewed to have a linearly positive influence on employability of individuals. However, as the recent research suggests the overall impact of such education on professional situation of graduates determined by various factors and nuances. In this study, using the mixed-methods approach I explored the employment experiences of graduates in the Kazakhstani labour market. The quantitative data were collected through a survey of 69 foreign-educated specialists working in Kazakhstan. The qualitative data were collected through the semi-structured interviews with twelve participants to inquire deeper into the effects of having foreign education in the Kazakhstani labour market, and to explore nuances related to their personal and professional labour market experiences. The employment experiences of graduates are conceptualised through the framework of human and social capitals and the signalling/screening theory. Findings illustrate that graduates view their foreign education as an advantageous endeavour in respect to the linguistic skills, transferable skills, and acquisition of useful networks. They also reported challenges in application of their international competences at work and limited options and capacity of the local labour market for professionals with international education experience. The findings of this paper have implications for policy and practice in relation to the applicability of internationally acquired knowledge and skills of graduates, the education of employers on the benefits of study abroad, and in informing prospective international students and their parents about risks and benefits of foreign education. This study contributes to our understanding of employment experiences of foreign-educated Kazakhstani graduates in the local labour market and highlights the need for further research in this area.
Keywords: Type of access: Restricted; study abroad; Kazakhstan; labour market; employability; foreign-educated specialists